Technology Champions: A Theory-Based Intervention to Improve Adoption of Occupational Safety Innovations. Issue 3 (2nd July 2016) - Weidman, Justin E.; Dickerson, Deborah E.; Koebel, C. Theodore
ABSTRACT: Prevention-through-design (PtD) is a new initiative to reduce occupational risks by developing lower-risk tools, equipment, methods, and materials. Once PtD innovations have been developed, the challenge is to have them adopted by industry. A theory-based intervention involving the creation of "technology champions" to improve construction firm adoption of a PtD innovation was developed, implemented, and tested. Technology Champions were created in firms through a methodology entitled "enhanced trialability." In a controlled pre-test/post-test experimental design, firm decision-maker (n=40) readiness to adopt the PtD innovation was assessed using a validated survey instrument. Enhanced trialability was successful in producing technology champions. Also, gain-score t-test analysis found significant improvements in 'innovation adoption readiness' among firms with technology champions, when compared to firms with no technology champions (p = .01). This intervention can be used by future researchers and occupational safety and health practitioners to improve adoption of safety innovations.